P6.026 Lack of Integration of PMTCT Services and Maternal Syphilis Screening and Treatment in Mwanza City-Tanzania. (13th July 2013) - Balira, R; Watson-Jones, D; Mabey, D; Ross, D A; Weiss, H
Abstract : Background: Integration of PMTCT and maternal syphilis screening and treatment is an efficient and cost-effective way of providing services to women at the point of delivery because it saves resources and providers' and clients' time. We documented the extent of integration of PMTCT and antenatal clinic (ANC) syphilis screening services in Mwanza city. Methods: Interviews were conducted with 89 health workers in 3 ANCs and in two maternity wards to collect information on key work activities, PMTCT training and syphilis management. Observations were made by the research team on 9 health education sessions, the client flow in ANCs and on the care of women admitted for delivery and who were not screened for syphilis during pregnancy. Results: Only 25% of ANC and maternity ward health workers had received training in both PMTCT and syphilis management. Generally, women attending for the first ANC visit for that pregnancy spent ≥ 3 hours at the clinic. The maximum distance covered within the facility while accessing services in the ANCs was 0.3 km. At one of the three ANCs, there was no PMTCT and syphilis service integration. All women who were not screened for syphilis at ANCs were not offered any screening at the maternity ward. In contrast 70% of women who had not been screened for HIV in pregnancy were screened at delivery Conclusion: Both PMTCT and maternal syphilis screening and treatment services are documented policies in Tanzania. However, the absence of integrated guidelines and protocols regarding syphilis screening within PMTCT services is a challenge for ANC and maternity ward service providers. Health workers at all levels of maternal care should be given training on implementation of integrated services for both prevention of syphilis and MTCT of HIV.